2010
DOI: 10.1002/humu.21154
|View full text |Cite
|
Sign up to set email alerts
|

Mutation update for theCSB/ERCC6andCSA/ERCC8genes involved in Cockayne syndrome

Abstract: Cockayne syndrome is an autosomal recessive multisystem disorder characterized principally by neurological and sensory impairment, cachectic dwarfism, and photosensitivity. This rare disease is linked to mutations in the CSB/ERCC6 and CSA/ERCC8 genes encoding proteins involved in the transcription-coupled DNA repair pathway. The clinical spectrum of Cockayne syndrome encompasses a wide range of severity from severe prenatal forms to mild and late-onset presentations. We have reviewed the 45 published mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
198
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(207 citation statements)
references
References 63 publications
7
198
1
1
Order By: Relevance
“…2B). However, when we used the CSA patient cell line (CS3BE) that harbors two point mutations on the CSA gene, which severely impairs the WD40 motif of CSA protein (18,20,24), we found that the UV-induced chromatin accumulation of KIAA1530 was abolished (Fig. 2C).…”
Section: Kiaa1530mentioning
confidence: 97%
See 2 more Smart Citations
“…2B). However, when we used the CSA patient cell line (CS3BE) that harbors two point mutations on the CSA gene, which severely impairs the WD40 motif of CSA protein (18,20,24), we found that the UV-induced chromatin accumulation of KIAA1530 was abolished (Fig. 2C).…”
Section: Kiaa1530mentioning
confidence: 97%
“…Eighteen distinct CSA mutations have been reported to date (24). Most of these point mutations and premature terminations lead to severe CS clinical manifestations, as described above (25).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The biochemical and molecular properties are detailed below. Mutational analysis among CS patients showed that for both genes ( 60% CSB and 40% CSA) mutations are scattered over the genes with, to date, no clear genotypephenotype correlation (Laugel et al 2010). …”
Section: Cockayne Syndrome (Cs)mentioning
confidence: 99%
“…PGBD3, one of the PiggyBac derived transposons in the human genome is abundantly expressed in such a fusion form with Cockayne syndrome B (CSB) protein (http://biogps.org/). CSB protein has functions in transcription-coupled nucleotide excision repair (Sarker et al, 2005;Laine and Egly, 2006) and chromatin remodeling (Newman et al, 2006), and mutations of the CSB gene are responsible for 70% of CS disease (Laugel et al, 2010). PGBD3 has been conserved in the 5th intron of CSB gene in Primates, and alternative splicing produces a protein fusion product with the N-terminal part of CSB protein (Newman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%